The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/mame.202200193
|View full text |Cite
|
Sign up to set email alerts
|

Materials and Manufacturing Methods for EWOD Devices: Current Status and Sustainability Challenges

Abstract: Electrowetting-on-dielectric (EWOD) devices have proven to be effective tools for precise microfluidic manipulation or in liquid lenses that surpass conventional solid lenses in versatility. However, the fabrication of these devices presents many challenges, such as their scalability or the growing concern on their environmental impact due to materials used in their fabrication. This review provides a comprehensive analysis of the materials currently used in the fabrication of EWOD devices and the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…It was observed that the double-layer structure effectively reduced the number of ion channels through both layers, which is a common approach in electrowetting display applications to improve the device lifetime (Figure 13a, insets). Moreover, the CTP dielectric layer exhibited lower leakage compared to commercial dielectric materials (HN photoresist or SU8) 63,64 in the double-layer device (Figure 13b). The single CTP layer-based device could stably switch between 0 and −40 V, where the turning point during switch-on was attributed to the oil reorientation in the pixel (Figure 13c).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…It was observed that the double-layer structure effectively reduced the number of ion channels through both layers, which is a common approach in electrowetting display applications to improve the device lifetime (Figure 13a, insets). Moreover, the CTP dielectric layer exhibited lower leakage compared to commercial dielectric materials (HN photoresist or SU8) 63,64 in the double-layer device (Figure 13b). The single CTP layer-based device could stably switch between 0 and −40 V, where the turning point during switch-on was attributed to the oil reorientation in the pixel (Figure 13c).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…9−11 unstable in the electric field generated by two parallel electrodes for a long time. 8,12 Dielectric liquid can be pulled into the air gap of two parallel electrodes when a voltage is applied to both electrodes. 13−15 A large number of scholars have studied the use of this phenomenon to liquid films unstable and have prepared various polymer array microstructures, such as some circular arrays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These adapting techniques on controllable polymer micropatterns provide advanced fabrication tools with high-precision capabilities but need sophisticated and costly processes and equipment. Since that electrowetting manipulation and movement/deformation of liquids can be driven only through the change or adjustment of the electrical signals, it exhibits very extraordinary high research value and attracts much research interest. It was discovered that dielectric liquid is unstable in the electric field generated by two parallel electrodes for a long time. , Dielectric liquid can be pulled into the air gap of two parallel electrodes when a voltage is applied to both electrodes. A large number of scholars have studied the use of this phenomenon to liquid films unstable and have prepared various polymer array microstructures, such as some circular arrays . Hwang et al fabricate periodic line microstructures at the submicron scale. , Vespini et al produced various microlens arrays .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation